2005
DOI: 10.1590/s1517-86922005000200005
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da natação associado a diferentes dietas sobre o músculo tibial anterior do rato: estudo morfológico e histoquímico

Abstract: The objective of this study was to investigate the effect of the association of different swimming program frequencies and diets on the characteristics of the anterior tibial muscle of 24 Wistar male rats. These rats were randomly assigned into three groups: untrained (control), trained group (two days/week) and trained group (five days/week). Each group was divided into two groups, which received one of the two normal or high calorie diets. After the training period, muscle samples were collected and frozen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
4
0
2
Order By: Relevance
“…Moreover, rounding processes of the fibers and the presence of necrosis and inflammatory infiltrates, especially in the animals submitted to the diet with commercial food and physical exercise and hypercholesterolemic diet and physical exercise, also indicate the possibility of myopathic scenario. The diets applied in the present study independently, do not interfere in the histological parameters, corroborating the findings by Ciabattari et al 18 , who analyzed the effect of swimming associated with different diets on the tibialis anterior muscle of Wistar rat.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, rounding processes of the fibers and the presence of necrosis and inflammatory infiltrates, especially in the animals submitted to the diet with commercial food and physical exercise and hypercholesterolemic diet and physical exercise, also indicate the possibility of myopathic scenario. The diets applied in the present study independently, do not interfere in the histological parameters, corroborating the findings by Ciabattari et al 18 , who analyzed the effect of swimming associated with different diets on the tibialis anterior muscle of Wistar rat.…”
Section: Discussionsupporting
confidence: 92%
“…Bonfim et al 20 also identified muscular alterations in the gastrocnemius muscle, with special attention to inflammatory infiltrate in all animals treated with commercial food and physical exercise. Actually, physical exercise per se only leads to injuries in the skeletal musculature, which on its turn, cause adaptive process, altering both shape and structure of the muscle fibers, as well as promoting inflammatory response 14,18 . In the muscular histological evaluation, considering the association between fluvastatin, simvastatin and physical exercise, it is concluded that it leads to morphological alterations with predominance in the use of simvastatin, ranging from light to severe level in the soleus muscle of rats, induced by the HMG-CoA redutase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the overloads during the training, weights of lead equivalent to 5% of the body mass were fixed to the thorax, which was checked and corrected weekly. Five weekly sessions lasting 60 min each were performed for 8 weeks in a total of 40 sessions (Ciabattari, Dal Pai, & Dal Pai, 2005).…”
Section: Aquatic Trainingmentioning
confidence: 99%
“…Experimento foi realizado para investigar o efeito da associação de diferentes frequências de programas de natação nas características do músculo tibial anterior de ratos 20 . Os autores concluíram que exercícios de natação exaustivos provocaram diferentes tipos de lesões morfoló-gicas nas fibras deste músculo como: splitting com alguns mionúcleos internos, atrofias de algumas fibras devido à desnervações, modulação e hipertrofia de fibras musculares, variações em seus diâmetros, citoplasmas com hipercontração e acentuado polimorfismo; algumas dessas alterações também foram observadas nos músculos sóleo e tibial anterior em nosso treinamento.…”
Section: Discussionunclassified